Review of the Effectiveness and Safety of Secukinumab Administration for the Treatment of Moderate to Severe Plaque Psoriasis - Mahariska, Dina Fitria; Rumawas, Marina Astrid; William, William; bah, Yasavati Kurnia (Jurnal MedScientiae, 2024)
Psoriasis is a chronic recurrent inflammation of the skin caused by excessive activity of the immune system. Based on data from WHO psoriasis cases are 0.09% - 11.43%, while in Indonesia it reaches 2.5% of the total population. Of the various types of psoriasis, the most common is plaque psoriasis or psoriasis vulgaris, up to 90%. The severity of moderate to severe plaque psoriasis is a problem because it affects both physical and psychological life. This study review aims to determine the effectiveness and safety of treatment with secukinumab in moderate to severe plaque psoriasis. Secukinumab is the choice because the main target of this biological agent is to neutralize IL-17A. Secukinumab is available in Indonesia and was approved by the FDA in 2015. Parameters of treatment success were seen from the PASI, DLQI and BSA scores. Side effects that often occur are nasopharyngitis, skin infections, upper respiratory tract infections and gastrointestinal disorders.